Excellent Result of Revision Total Hip Replacement with Unexpected Metallosis - azmi farhadi; Kukuh Dwiputra Hernugrahanto; Jifaldiafrian Maharajadinda Sedar; Mohammad Zaim Chilmi (The Hip and Knee Journal, 2021)
ABSTRACT Background: Metallosis is a syndrome of metal-induced synovitis with infiltration and accumulation of metallic debris into the periprosthetic structures, including soft and bony tissues. The debris causes a chronic inflammatory reaction due to joint instability, pain, osteolysis, implant loosening, or implant failure. The absence of a specific sign or symptom that indicates metallosis causes difficulty to diagnose.Presentation of Case: A 35-year-old female, history of primary left total hip replacement since seven years ago after avascular necrosis of the femoral head, presented with an eight-month history of left hip pain and limited range of motion. Radiograph results showed that there is no evidence of periprosthetic fracture or infection. The patient underwent a left revision total hip replacement, which revealed extensive necrotic black metal debris throughout the joint space.Discussion: Effective treatment requires a revision of total hip replacement to remove metal debris, bone graft area osteolysis, and to address the mechanical failure. The greatest possible of metallic debris during debridement is vital to avoid further osteolysis and prevent more extensive damage. Excellent clinical result was evaluated by Harris’s hip score in 18 months postoperatively.Conclusion: This case is a rare example of chronic metallosis presenting seven years following total hip replacement. Revision total hip replacement is the consensus management choice to avoid further destruction of the bone and joint capsule that can occur with metal-induced inflammation. Keywords: